2013
DOI: 10.1371/journal.pone.0081337
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection of Tuberculous Mycobacteria in Animal Tissues Using a Semi-Nested Probe-Based Real-Time PCR

Abstract: Bovine tuberculosis has been tackled for decades by costly eradication programs in most developed countries, involving the laboratory testing of tissue samples from allegedly infected animals for detection of Mycobacterium tuberculosis complex (MTC) members, namely Mycobacterium bovis. Definitive diagnosis is usually achieved by bacteriological culture, which may take up to 6–12 weeks, during which the suspect animal carcass and herd are under sanitary arrest. In this work, a user-friendly DNA extraction proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 34 publications
8
36
0
Order By: Relevance
“…In this species, the inhalation of contaminated droplets through cough or nasal secretion of an animal with active pulmonary tuberculosis is most likely to cause infection (NEILL et al, 1994). Concerning the distribution of lesions, the findings in this study are in line with those reported by Costa et al (2013) who observed focal, multifocal, or diffuse nodular lesions.…”
Section: Resultssupporting
confidence: 90%
“…In this species, the inhalation of contaminated droplets through cough or nasal secretion of an animal with active pulmonary tuberculosis is most likely to cause infection (NEILL et al, 1994). Concerning the distribution of lesions, the findings in this study are in line with those reported by Costa et al (2013) who observed focal, multifocal, or diffuse nodular lesions.…”
Section: Resultssupporting
confidence: 90%
“…Other researchers who made similar use of nested PCR analysis reported similar (COSTA et al, 2013) or even higher increase in detection of positive samples (ARAÚJO et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…(COSTA et al, 2013). The occurrence of nodular granulomatous lesions are typical of this infirmity (FURLANETTO et al, 2012).…”
Section: Abstract: Infectious Diseases; Mycobacterium Bovis;mentioning
confidence: 93%
“…Ultrapure water was used as negative control and DNA from a culture of B. burgdorferi sensu stricto B31 strain was used as positive control. To insure no inhibitory compounds affected the nested-PCR reaction, a conventional PCR targeting the mammalian b-actin housekeeping gene (primers F_Actin/ R_Actin) was used as an internal control (Costa et al 2013).…”
mentioning
confidence: 99%